Production Management Model for the Evaluation of Operator's Posture-Base Measurement and to Redesign Work Area to Improve Labor Productivity in a Manufacturing SME - Chacara-Barrera, Katherine (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.